2013
DOI: 10.2478/s11756-013-0193-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and PAH growth abilities of bacterial strains isolated from a contaminated soil in Slovakia

Abstract: Different abandoned industrial areas contaminated by polycyclic aromatic hydrocarbons (PAHs) are present in Slovakia. These environmental burdens are very dangerous to the health of human and environment. The bioremediation, based on the use of hydrocarbons degrading microorganisms, is a promising strategy to sanitize these polluted sites. The aim of this investigation was to assess the bacterial diversity of a PAHs-contaminated soil and to select the potential hydrocarbonoclastic bacteria which can be used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…It is well documented that various bacteria from genus Pseudomonas, including P. aeruginosa strains, inhabit hydrocarbon-contaminated soils and can break a wide range of different organic compounds (Glick et al 1994;Hong et al 2005;Saikia et al 2012;Pacwa-Płociniczak et al 2014). They are the well-known bacteria that have the capability of utilizing a number of aliphatic and aromatic hydrocarbon compounds as a carbon and energy sources (Das and Chandran 2010;Kadali et al 2012;Puškárová et al 2013). Monitoring of maximum biosurfactant production and reduction in surface tension during growth of P. aeruginosa DSVP20 on pristane, eicosane, and fluoranthene at intervals of 24 h revealed that with increase in dry biomass, there was a reduction in This coincides with the maximum biosurfactant production (g/l) 6.315, 6.813, and 3.932 on pristane, eicosane, and fluoranthene, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that various bacteria from genus Pseudomonas, including P. aeruginosa strains, inhabit hydrocarbon-contaminated soils and can break a wide range of different organic compounds (Glick et al 1994;Hong et al 2005;Saikia et al 2012;Pacwa-Płociniczak et al 2014). They are the well-known bacteria that have the capability of utilizing a number of aliphatic and aromatic hydrocarbon compounds as a carbon and energy sources (Das and Chandran 2010;Kadali et al 2012;Puškárová et al 2013). Monitoring of maximum biosurfactant production and reduction in surface tension during growth of P. aeruginosa DSVP20 on pristane, eicosane, and fluoranthene at intervals of 24 h revealed that with increase in dry biomass, there was a reduction in This coincides with the maximum biosurfactant production (g/l) 6.315, 6.813, and 3.932 on pristane, eicosane, and fluoranthene, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…was found to contain genes responsible for carbazole degradation. Additionally, it can regulate certain classes of pesticides such as dibenzo-p-dioxins and remediate heavy metals (Puškárová et al 2013). It also possesses the potential to accumulate intracellular Zn 2+ , and reduction of Cd 2+ uptake enhanced the expression of the low-molecular weight cysteine-rich protein metallothionein, which sequesters heavy metals and their binding via associated proteins .…”
Section: Resultsmentioning
confidence: 99%
“…Sphingomonas sp. has recently been shown to help in the degradation of persistent metabolites in the environment (Puškárová et al 2013). Sphingomonas sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthrobacter spp. have been reported to degrade various hydrocarbons, including aromatic hydrocarbons (Stevenson 1967) and PAHs (Puškárová et al 2013). Additionally, Arthrobacter spp.…”
Section: Occurrence Of Known Oil-degrading Bacteriamentioning
confidence: 99%